HBsAg and HBcrAg as predictors of HBeAg seroconversion in HBeAg‐positive patients treated with nucleos(t)ide analogues. Issue 8 (2nd April 2018) - Wang, B.; Carey, I.; Bruce, M.; Montague, S.; Dusheiko, G.; Agarwal, K.
Summary: HBeAg seroconversion marks an important spontaneous change and treatment end‐point for HBeAg‐positive patients and is a pre‐requisite for HBsAg loss or functional cure. In this retrospective analysis, we aimed to identify predictors of seroconversion using serum quantitative HBsAg and HBcrAg, in HBeAg‐positive patients treated with nucleos(t)ide analogues (NA). Data and samples from 118 HBeAg‐positive adults (genotypes A‐G) started on NA between Jan 2005 and Sept 2016 were retrospectively analysed at several time‐points. The predictive power of on‐treatment levels of HBsAg and HBcrAg was determined using receiver operating curve (ROC) analysis and cut‐off values determined by maximized Youden's index. About 36.4% of patients achieved HBeAg seroconversion after a median of 39 months' treatment. On treatment kinetics of HBV DNA, HBsAg and HBcrAg differed between HBeAg seroconverters and nonseroconverters. A combination of HBsAg and HBcrAg had the greatest predictive value for HBeAg seroconversion: at 6 months, HBsAg of 3.9 log10 IU/mL and HBcrAg of 5.7 log10 U/mL had a sensitivity of 71.4%, specificity of 79.5%, positive predictive value (PPV) of 65.2% and negative predictive value (NPV) of 83.8%, with AUROC of 0.769 (0.668, 0.869; 95%CI), and at 12 months, HBsAg 3.8 log10 IU/mL and HBcrAg 5.5 log10 U/mL had a sensitivity of 73.7%, specificity of 79.5%, PPV of 63.6% and NPV of 86.1%, with AUROC 0.807 (0.713, 0.901; 95% CI). In conclusion, our results may be used to identify patients who are unlikely to achieve treatment end‐points, which will be important as the future management of chronic hepatitis B looks to therapies that offer functional cure.